Test of Weak Form Efficiency: An Empirical Study of the Malaysian Foreign Exchange Market - Lim, Pei Mun (2011)
This paper empirically tests the Efficient Market Hypothesis (EMH) in the weak sense for the Malaysian foreign exchange market. The hypothesis is tested using two ways. First is by testing the random walk hypothesis based on individual unit root test and second is by testing the profitability of simple technical trading rules. The study covers the high frequency daily data from January 1997 to December 2010 and the spot exchange rates are quoted as Malaysian Ringgit per unit of US Dollar. Due to the adoption of fixed exchange rate regime of the Malaysia currency, about seven years of data from September 1998 to end of July 2005 have been dropped from the sample period. A total of 1855 daily data is separated into three distinct subsamples in order to enable subsample analysis. The results are salient for three subsamples but contradiction occurs between the unit root test and the test of profitability of moving average rules. The first hypothesis of random walk series is rejected indicating that the exchange rate changes do not follow a random walk movement. On the other hand, the second hypothesis of zero excess return for moving average rules is not rejected. The finding contradicts with the ordinary course of market efficiency in which technical analysis is able to generate supernormal profits when the market is in weak form inefficient. Hence, the Malaysian foreign exchange market fails to be classified as weak form efficient due to the significant inefficient evidence found. However, behavioral finance theory could explain the absence of predictive power of moving average rules.